The effects of different lung parts, age, and batches on the lung microbiota of healthy rats - Ping Chen; Tingting Hu; Haonan Jiang; Bing Li; Guiying Li; Pixin Ran; Yumin Zhou (Annals of Medicine, 2024)
Background Rat models are valuable tools to study the lung microbiota in diseases. Yet the impacts of different lung parts, young and mature adult stages, and the different batches of the same conditions on the healthy rat lung microbiome have not been investigated.Methods The rat lung microbiome was analyzed to clarify the lung part-dependent and age-dependent differences and to evaluate the effects of several ‘batch environmental factors’ on normal rats, after eliminating potential contamination.Results The results showed that the contamination could be identified and excluded. The lung microbiome from left and right lung parts was very similar so one representative part could be used in the microbiome study. There were significantly different lung microbial communities between the young and mature adult groups, and also between the different feeding batches groups of the same repetitive feeding conditions, but a common lung microbiota characterized by Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria as the most dominant phyla were present in all adult rats. It indicated that the experiment under the same condition of the same rats batch was needed to compare the difference in the lung microbiota and repeated experiments were necessary to confirm the results.Conclusion These data represented that the lung bacterial communities were dynamic and rapidly susceptible to environmental influence, clustered strongly by age or different feeding batches but similar in the different lung tissue parts. This study improved the basic understanding of the potential effects on the lung microbiome of healthy rats.